Degradation of subunits of the Sec61p complex, an integral component of the ER membrane, by the ubiquitin-proteasome pathway. - Biederer, T (1996)
We have investigated the degradation of subunits of the trimeric Sec61p complex, a key component of the protein translocation apparatus of the ER membrane. A mutant form of Sec6lp and one of the two associated proteins (Sss1p) are selectively degraded, while the third constituent of the complex (Sbh1p) is stable. Our results demonstrate that the proteolysis of the multispanning membrane protein Sec61p is mediated by the ubiquitin-proteasome pathway, since it requires polyubiquitination, the presence of a membrane-bound (Ubc6) and a soluble (Ubc7) ubiquitin-conjugating enzyme and a functional proteasome. The process is proposed to be specific for unassembled Sec61p and Sss1p. Thus, our results suggest that one pathway of ER degradation of abnormal or unassembled membrane proteins is initiated at the cytoplasmic side of the ER.